Yeah! - Bagge, Peter 1957- (Fantagraphics, 2011)
The all-girl band Yeah!--consisting of Krazy, Honey, and WooWoo--have achieved intergalactic stardom on every planet except Earth, where they struggle to achieve fame in suburban New Jersey